KEMAMPUAN PENALARAN ADAPTIF SISWA SMP se-KOTA PONTIANAK - Yadi Ardiawan; Nurmaningsih Nurmaningsih (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2018)
This study aims to reveal the ability of adaptive reasoning of junior high school students in Pontianak, which is divided into categories of secondary, middle and lower schools. This research is descriptive research with research form is survey. Sampling in this research using stratified cluster random sampling technique. Of the 23 existing schools thereafter were randomly assigned to each school to represent high school, middle class, and low school. Categorization of schools based on the value of students National Exam. Based on the result of research analysis, it is found that the average of adaptive reasoning ability of junior high school students in Pontianak is 42,96% with enough category. While the average adaptive reasoning ability of high, medium and low students is 48.82% (enough), 41.06% (enough), and 39% (enough), respectively.